Amazonian biogenic volatile organic compounds under global change. (24th June 2020) - Yáñez‐Serrano, Ana M.; Bourtsoukidis, Efstratios; Alves, Eliane G.; Bauwens, Maite; Stavrakou, Trissevgeni; Llusià, Joan; Filella, Iolanda; Guenther, Alex; Williams, Jonathan; Artaxo, Paulo; Sindelarova, Katerina; Doubalova, Jana; et al.
Abstract: Biogenic volatile organic compounds (BVOCs) play important roles at cellular, foliar, ecosystem and atmospheric levels. The Amazonian rainforest represents one of the major global sources of BVOCs, so its study is essential for understanding BVOC dynamics. It also provides insights into the role of such large and biodiverse forest ecosystem in regional and global atmospheric chemistry and climate. We review the current information on Amazonian BVOCs and identify future research priorities exploring biogenic emissions and drivers, ecological interactions, atmospheric impacts, depositional processes and modifications to BVOC dynamics due to changes in climate and land cover. A feedback loop between Amazonian BVOCs and the trends of climate and land‐use changes in Amazonia is then constructed. Satellite observations and model simulation time series demonstrate the validity of the proposed loop showing a combined effect of climate change and deforestation on BVOC emission in Amazonia. A decreasing trend of isoprene during the wet season, most likely due to forest biomass loss, and an increasing trend of the sesquiterpene to isoprene ratio during the dry season suggest increasing temperature stress‐induced emissions due to climate change. Abstract : We review the current information on Amazonian biogenic volatile organic compounds (BVOCs) and identify future research priorities. Then we propose a feedback loop between Amazonian BVOCs and the trends of climate and land‐use changes in Amazonia which is further supported by satellite observations and model simulation time series showing a combined effect of climate change and deforestation on BVOC emission in Amazonia.